NON-INFECTIOUS FACTORS ASSOCIATED WITH PRE-WEANING MORTALITY IN PIGLETS - Kramarenko, A. S.; Kramarenko, S. S. (Scientific Progress & Innovations, 2021)
The objective of this study was to evaluate the effect of different factors of non-infectious nature on piglet pre-weaning mortality. This study was conducted on the commercial pig farm of “Tavriiski svyni”, LLC, located near Skadovsk (Kherson region, Ukraine). The experimental materials used for this study consisted of 100 individuals of productive parent sows of the Large White breed. The number of piglets that died between birth and weaning and frequency of piglets that died between birth and weaning per litter, the total number of piglets born and prolificacies were monitored in the first eight farrows during the period of eleven years (2007–2017). Piglets that died between birth and weaning were observed in 55.4 % of the litters. The piglet pre-weaning mortality level observed in our study (12.7±0.6 %) was within the range of rates (10 to 20 %) reported for commercial pig farms in other countries of the world. With increasing age of the sow (farrowing’s number), there was a gradual decrease in the frequency of litters that did not have piglets that died between birth and weaning (χ2=21.85; df=7; P=0.003) and, on the contrary, a gradual increase in the litters that had 5 and more piglets that died between birth and weaning (χ2=15.24; df=7; P=0.031. In general, a significant effect of farrow number on the distribution of litters with different numbers of piglets that died between birth and weaning was observed (χ2=39.38; df=24; P=0.028). The lowest number (and frequency) of piglets that died between birth and weaning was registered among sows that had 7–8 piglets (alive + dead) born per litter. Sows with smaller litter sizes did not have pre-weaning mortality. The binary logistic regression analysis indicated that the probability of a piglet dying between birth and weaning was significantly associated with the number of the sow’s farrowing (χ2=11.60; P<0.001), total number of piglets born (χ2=277.19; P<0.001) and, to the greatest extent, with its prolificacy (χ2=378.21; P<0.001). In the latter case, this model predicted well the probability of a piglet dying between birth and weaning (in 84.0 % of cases) and more or less adequately predicted its survival (in 73.9 % of cases). The multiple linear regression analysis indicated that the frequency of piglets that died between birth and weaning per litter was significantly associated with the total number of piglets born and prolificacy (F(2; 797) = 147.07; P<0.001). At the same time, the estimation of the partial correlation coefficient for prolificacy was almost twice as high (rP=0.233; P<0.001) than for the total number of piglets born (rP=0.124; P<0.001).